Asupan vitamin A, vitamin C, vitamin E, BCAA dan kaitannya dengan kadar hs-CRP pada member fitness center dewasa - Qoniatu Zulfa; Deny Yudi Fitranti; Hartanti Sandi Wijayanti; Etika Ratna Noer (AcTion: Aceh Nutrition Journal, 2023)
Excessive physical exercise can stimulate proinflammatory cytokines expressions and increases high sensitivity C-Reactive Protein (hs-CRP). Branched Chain Amino Acids (BCAA) and vitamins A, C, and E are antioxidant mechanisms to reduce oxidative stress. This study analyzes the correlation between vitamin A, C, E, and BCAA intake with hs-CRP. The study design was cross-sectional, which was conducted in Semarang. Participants were 48 men aged 20-43 years. Sampling used consecutive sampling. Data were collected using food recall 3x24h to assess dietary intake and laboratory tests using the Immunoturbidimetric method to determine hs-CRP levels. Data were statistically analyzed using Spearman-Rank and multiple linear regression. The result showed that the subject with high-risk categories of hs-CRP was 18,8%. The intake of BCAA was 10,8% from supplements. Most subjects had an excessive intake of vitamin A but did not meet the needs of vitamins C and E. There was no correlation between BCAA intake (p= 0,681) and vitamin C intake (p= 0,137) with hs-CRP levels. However, there was a negative correlation between vitamin A (p= 0,003) and vitamin E (p= 0,013) intake with hs-CRP levels. Multivariate analysis showed that the intake of vitamin A associated with hs-CRP levels of 8,1% (p= 0,028). In conclusion, vitamin A intake is the most influential factor in hs-CRP levels in fitness center members.